Zuo Gui Wan Alters Expression of Energy Metabolism Genes and Prevents Cell Death in High-Glucose Loaded Mouse Embryos. (25th June 2018) - Liang, Qi; Qu, Zhipeng; Liang, Yu; Feng, QianJin; Niu, Xin; Bai, Temaka; Wang, Yingli; Song, Qiang; Adelson, David L.
Abstract : Background . Zuo Gui Wan (ZGW) is a classic formula in traditional chinese medicine (TCM). Previous studies have shown that it is beneficial for impaired glucose tolerance (IGT) of adults and the offspring as well. This study aimed to understand the molecular mechanisms of the efficacy of ZGW on IGT. Methods . We used high-glucose loaded 2-cell stage mouse embryos as a model and took advantage of single-cell RNA sequencing technology to analyze the transcriptome of the model with or without ZGW. Differential gene expression analysis was performed with DESeq2. Results . High glucose can downregulate genes in the ribosome pathway, while ZGW can reverse this inhibition and as a result prevent embryo cell death caused by high glucose. Furthermore, high glucose can affect sugar metabolism and influence mitochondrial function, but ZGW can promote sugar metabolism via the tricarboxylic acid cycle mainly through upregulating the genes in the respiratory chain and oxidative phosphorylation. Conclusions . ZGW had a protective effect on embryonic cell death caused by glucose loading. The reversion of inhibition of ribosome pathway and regulation of mitochondrial energy metabolism are main effects of ZGW on high-glucose loaded embryos. This research not only revealed the global gene regulation changes of high glucose affecting 2-cell stage embryos but also provided insight into the potential molecular mechanisms of ZGW on the IGT model.